P8 Objective Cough Frequency Monitoring In Bronchiectasis. (10th November 2014) - Spinou, A; Garrod, R; Lee, KK; Elston, C; Loebinger, MR; Chung, KF; Wilson, R; Birring, SS
Abstract : Introduction and objectives: Cough is a major symptom in bronchiectasis. Cough monitors are emerging as an important tool that assesses cough objectively. The aim of this cross-sectional study was to assess cough frequency in non-cystic fibrosis bronchiectasis, investigate its association with patient-reported symptoms and health-related quality of life (HRQOL), and investigate potential factors of cough frequency variability. Methods: Patients with non-cystic fibrosis bronchiectasis were recruited from 2 outpatient bronchiectasis clinics. All patients underwent 24-hour ambulatory cough monitoring with the Leicester Cough Monitor, and reported sleeping time in a diary. The patients also completed the Leicester Cough Questionnaire (HRQOL), and visual analogue score (VAS) for sputum and cough severity. Sputum bacteria colonisation status was assessed, and defined as at least 2 positive cultures, minimum 3 months apart and within one year. Results: 49 patients were recruited; median (IQR) age 65 (52, 70) years, 64% female. The aetiology of bronchiectasis were: idiopathic (45%), post infective (29%) and other (25%). The prevalence of sputum colonisation were: pseudomonas aeruginosa 38% and other organisms 29% of patients. Median (IQR) 24-hour, day time and night time cough counts were: 249 (112, 438), 240 (109, 404.5) and 24 (5, 56.5) coughs respectively. There was diurnal variation in cough frequency (Figure 1 ). Day time cough frequency was significantly greater than night time (Wilcoxon signed rank test p < 0.01). 24-hour total coughs were significantly associated with HRQOL (Spearman ρ=-0.54, p < 0.01), cough VAS (ρ=0.56, p < 0.01) and sputum VAS (ρ=0.48, p < 0.01). There was an association between 24-hour cough counts and gender (linear regression p = 0.05), but no association with bronchiectasis aetiology, sputum colonisation status or age. Conclusions: Cough frequency monitoring in patients with bronchiectasis is feasible. Higher cough frequency was associated with poorer HRQOL and worse patient-reported symptoms of cough and sputum. Patients coughed more during the day than at night. 24-hour cough frequency was variable and gender was identified as an influential factor. Future studies should investigate other potential factors for cough variability in bronchiectasis and evaluate the potential of cough frequency as an outcome measure for assessing the efficacy of therapy.